Liquid crystal display modes in a nontilted bent-core biaxial smectic liquid crystal - Vij, Jagdish; Panarin, Yuri (My University, 2010)
Liquid crystal display (LCD) modes associated with the rotation of the secondary director in nontilted, biaxial smectic phase of an achiral bent-core compound are demonstrated. For LCDs, we find that at least four display modes are possible using SmAPA phase of the studied material, in which the minor directors in adjacent layers are aligned antiferroelectrically. The advantages of these modes include low driving field (1-2 V/?m), high contrast ratio 1000:1, relatively fast switching time of 0.5 ms and continuous gray scale. The molecular short axis or the polar axis in a negative dielectric, biaxial material is oriented by the in-plane electric field by a combination dielectric biaxiality and polarity at low electric fields and polarity at higher fields
PUBLISHED
Keywords: liquid crystal